Landform Classification which Alighted from Digital Elevation Models: Case in Citarum Watershed, Cilalawi Sub Watershed, West Java - Salwati, .; Saidi, Busyra Buyung (JOURNAL OF TROPICAL SOILS, 2008)
Application of GIS technology (Geographic Information System), that is Digital Elevation Models (DEMs) for the analysis of  landform or slope have been conducted in the Citarum watershed, Purwakarta West Java Province from August until November 2003. Research aim to make landform classification of DEMs use classification of ISODATA and   to evaluate the quality of landform classification which alighted from DEMs. To reach the target have been made DEMs, is later then degraded to become map set of regional form. DEMS made from contour map scale 1 : 25.000 with inteval of 12.5 m use Arcview version 2.65 with resolution of 25 m, and slope classification made software of ER Mapper. Field observation conducted for validation result of classification. Result of research indicate that wave landform (slope 8-15%) and hilly (slope 15-30%) in sub watershed of Cilalawi is DEMs have lower level class of fact in the field. While set of regional form level of (slope < 3%), waving (slope 3-8%) and have mount (slope > 30%) in sub of DAS Cilalawi have bevel class which almost is equal to fact in the field. Result of the  research indicated that map of landform or alighted from slope is DEMs not entirely as according to situation in fact of the field. Interconnected the mentioned sliver with quality map of used contour. Thereby verification in field is absolutely needed.